2020
DOI: 10.3892/br.2020.1312
|View full text |Cite
|
Sign up to set email alerts
|

Two-component signaling pathways modulate drug resistance of

Abstract: As the issues surrounding antibiotic-resistant strains of Staphylococcus aureus (S. aureus) are becoming increasingly serious concerns, it is imperative to investigate new therapeutic targets to successfully treat patients with S. aureus infections. The two-component signal transduction system is one of the primary pathways by which bacteria adapt to the external environment, and it serves an important role in regulating virulence gene expression, cell wall synthesis, biofilm formation and bacterial activity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…In a previous study, we demonstrated that the essential YycFG TCS was closely related to biofilm formation and extracellular matrix organization [ 16 ]. However, since the YycFG TCS is essential to S. aureus viability, the construction of deletion mutants of YycFG was unsuccessful [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we demonstrated that the essential YycFG TCS was closely related to biofilm formation and extracellular matrix organization [ 16 ]. However, since the YycFG TCS is essential to S. aureus viability, the construction of deletion mutants of YycFG was unsuccessful [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…TCS is one of the dominating pathways by which bacteria adapt to the external environment, and it plays an important role in regulating the formation of bacterial biofilms, the expression of virulence genes, the synthesis of the cell wall, and bacterial activity [ 30 ]. Generally, multiple mechanisms exist in the TCS, such as cross-regulation, integration, and coordination of various input stimuli to control biofilm formation [ 31 ]. Sucrose, a substrate for the synthesis of extracellular polysaccharides but not oligosaccharides, is beneficial for biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
“…Two-component regulatory systems (TCSs) exist ubiquitously in bacteria to adapt to stimuli and nutrition alterations from the external environment [11,12]. Typically, the TCS contains a histidine kinase (HK), which can autophosphorylate a conserved histidine residue in response to extracellular stimulus, and a response regulator (RR), which can transfer the phosphoryl group from HK [13].…”
Section: Introductionmentioning
confidence: 99%